PENGARUH MERK, KUALITAS PRODUK DAN PERSEPSI HARGA TERHADAP KEPUTUSAN PEMBELIAN GETAS 3 MERPATI - Krisna, Rio; Medinal; Tri Setyo Mulyani, Hendarti (Jurnal Progresif Manajemen Bisnis, 2020)
This study aims to determine the effect of brand variables, product quality and price perceptions on the purchase decision of getas 3 Merpati which is located at Jalan Harapan Bokor No. 276. The method used in this research is quantitative descriptive method. The population that is the subject of this research is the people of Sungailiat city who have bought getas 3 Merpati. The technique used in this research is random sampling technique. The number of samples in this study were 60 respondents. Data collection methods in this study used a questionnaire method with interval and likert scale. The data analysis technique used is multiple linear regression analysis techniques. The multiple linear regression analysis test used in this study includes: partial test (t test), simultaneous test (F test) and coefficient of determination test (R2). Hypothesis testing used is coefficient analysis to determine the relationship between research variables. Based on the results of this study concluded that: product quality variables and price perceptions have a positive effect and partial effect on the purchase decision of getas 3 Merpati while brand variables have a negative effect and do not have a partial effect on the purchase decision of getas 3 merpati. Variable brand, product quality and price perception based on the results of the study simultaneously influence the purchase decision of getas 3 Merpati.